2019
DOI: 10.14202/vetworld.2019.1826-1832
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and histopathological confirmation of clinically diagnosed lumpy skin disease in cattle, Baghdad Province of Iraq

Abstract: Aim: This study aimed to confirm the clinically diagnosed cattle with lumpy skin disease (LSD) at Baghdad Province/Iraq from October 2018 to March 2019. Materials and Methods: Molecular polymerase chain reaction (PCR) and histopathology were applied for the detection of LSD among 71 infected cattle issued for slaughter. Results: Pre-slaughter clinical examination showed significant increases (p<0.05) in values of temperature (39.7±0.74°C), pulse (96.42±3.51), and respiratory (33.54±0.63) rates. Enlargement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Those clinical signs were comparable with other previous descriptions [5,24,25]. Furthermore, the present work showed that the disease was most prevalent in the age group between 2 and 4 years, and this came in agreement with Gharban et al [26], who attributed the lowest infection attack among cattle less than 2 years because of passive maternal immunity that protects calves from LSDV infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those clinical signs were comparable with other previous descriptions [5,24,25]. Furthermore, the present work showed that the disease was most prevalent in the age group between 2 and 4 years, and this came in agreement with Gharban et al [26], who attributed the lowest infection attack among cattle less than 2 years because of passive maternal immunity that protects calves from LSDV infection.…”
Section: Discussionsupporting
confidence: 93%
“…The variation in the histological findings of LSD among infected cattle has also been described Available at www.veterinaryworld.org/Vol.14/August-2021/32.pdf by Tuppurainen et al [21]. Similar results to our findings were previously observed by Gharban et al [26], who reported that replication of the virus is accompanied by the formation of intracytoplasmic inclusion bodies in skin lesions of infected cattle. Furthermore, Prozesky and Bernard [31] concluded that vasculitis and thrombosis leading to edema and necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Lumpy skin disease (LSD) is an acute to chronic bovine viral disease caused by LSD virus (LSDV) that classified under Capripox genus of Poxviridae family (Gharban et al, 2019). Initially, the disease that first reported in 1929 in Zambia is suspected to be resulted by either poisoning or hypersensitivity to an insect bite, until the infectious nature was recognized in 1943 (Koirala et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, prevention of infection and protection of susceptible animals can be made by vaccination; whereas, supportive treatment for infected ones can effectively reduce the effects of disease (Babiuk, 2018;Zhugunissov et al, 2020). At the field, presumptive diagnosis depends mainly on the typical clinical signs and postmortem examination; whereas, at the laboratory, a combination of histopathological findings with the confirmatory techniques such as electron microscopy, serology, and molecular assays, and viral isolation can provide a definitive detection for LSDV (Abdallah et al, 2018;Gharban et al, 2019;Flannery et al, 2021). Polymerase chain reaction (PCR) is one of the most useful molecular tests which applied routinely to identify and confirm Capripoxvirus with high sensitivity and specificity (Sudhakar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation